Case Study of Heat Transfer on Heater Performance of Injection Molding Machines Before and After Maintenace - Surindra, Mochamad Denny; Su”™udy, Ahmad Hamim; Hermawan, Baktiyar Mei; Aulia, Nur Fatowil; Priyoatmojo, Slamet; Sumarno, F. Gatot; Suwoto, Gatot (Eksergi, 2022)
Injection molding is a thermoplastic material forming method in which the material melted by heating is injected by a plunger into a water-cooled mold so that it hardens. Molding companies have a classic problem with heaters used to heat plastic ores. One of the companies using the Yizumi UN160SK Injection Molding Machine with polystyrene plastic ore faced a heater malfunction that disrupted the production process.A case study of heater performance was carried out to find out signs of damage, what condition the heater was in (electricity consumption, heat generated and the condition of the plastic ore melt).